1994
DOI: 10.1016/0885-3924(94)90175-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in postoperative pain severity among four ethnic groups

Abstract: Subjects (N = 543) reporting on acute postoperative dental pain were classified into four major ancestral groups: Asian (N = 96), black American (N = 65), European (N = 296), and Latino (N = 88). Pain severity was measured using a 10-cm visual analogue scale following a standardized operative procedure. The subjects of European descent reported significantly less severe pain than those of black American or Latino descent. They also reported less pain than Asians, although this finding did not reach significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 25 publications
5
90
0
5
Order By: Relevance
“…2 1 Faucett et al demonstrated that patients of European descent rated postoperative dental pain less severely than patients of African and Latin descent. 22 Differing from previous studies conducted in this area, our study was conducted in Taiwan with a Chinese population of Eastern socio-cultural background as the study group. The distinct racial and cultural differences between various studies may have some bearing upon pain perception and expression, 23,24 with concomitant variation with respect to some results.…”
Section: Discussionmentioning
confidence: 99%
“…2 1 Faucett et al demonstrated that patients of European descent rated postoperative dental pain less severely than patients of African and Latin descent. 22 Differing from previous studies conducted in this area, our study was conducted in Taiwan with a Chinese population of Eastern socio-cultural background as the study group. The distinct racial and cultural differences between various studies may have some bearing upon pain perception and expression, 23,24 with concomitant variation with respect to some results.…”
Section: Discussionmentioning
confidence: 99%
“…Pain measures included VAS at one and three days postoperatively and analgesic use; while psychological measures included STAI, VAS (anxiety), General Health 17 found that personality characteristics are unrelated to postoperative pain following a study on 100 patients undergoing surgical removal of impacted third molars. Faucett et al 18 conducted a study to examine differences in severity of postoperative pain among 543 patients from four ethnic groups (Asian, Black American, European and Latino). The results showed that women and younger patients reported more pain, and subjects of European descent reported less pain than those of Black American and Latino descent.…”
Section: Dental Pain Without Psychological Manipulationmentioning
confidence: 99%
“…[16][17][18][19] Of these, three examined the predictive capacity of psychosocial factors on postoperative pain and recovery following surgical removal of third molars. One study found psychological factors, including postoperative anxiety, to predict postoperative pain.…”
Section: Dental Pain Without Psychological Manipulationmentioning
confidence: 99%
“…Também na dor crônica, o paciente preto sofre mais do que o branco, embora demore na procura da ajuda médica 56,57 . A deficiência da desidrogenase torna o negro mais sensível ao etanol 16 .…”
Section: Iv) Sistema Nervoso Centralunclassified